ARIES App in Academic Writing Class: Technology Acceptance Model (TAM) Analysis - Imran, Muhammad Chairil; Mursidin, Muthmainnah (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
The research aims to investigate ARIES app acceptance in academic writing class. In the university, one of the skills that must be learned is academic writing. Most jobs require strong academic writing skill, lecturers are obligated to equip students to become professional writers to enter the future career. The various applications provide benefits for students, the fact that students spend more time in existing technology and show mastery of information technology provide opportunities for lecturers to motivate students who have no motivation to write. Lecturers have implemented ARIES (Assisted Revision In English Style) to improve students academic writing, the researchers explore Technology Acceptance Model (TAM) which is intended to analyze the acceptance of students on information system. The total samples are 25 students from English education department Universitas Islam Makassar. The data were collected through questionnaire and interview. The finding shows that there was a positive response to the acceptance of Aries App in all contexts, Aries App provided new atmosphere for students in academic writing. Additionally, from interview, students emphasized that using the Aries App made students possible to complete academic writing given by the lecturer anywhere and anytime. In the conclusion, the students acceptance of Aries App relates to behavior performed by students.